2019
DOI: 10.1016/j.jbo.2019.100240
|View full text |Cite
|
Sign up to set email alerts
|

Have the difficulties and complications of surgical treatment for chondroblastoma of the adjoining knee joint been overestimated?

Abstract: Background and objective Chondroblastoma is difficult to treat as the tumor is surrounded by both articular cartilage and the epiphyseal plate. The differences in joint shape further complicate the problem. This retrospective study evaluates the efficacy of intraregional aggressive curettage and allogeneic bone grafting for treating chondroblastoma of the adjoining knee joint. Methods From February 2010 to February 2017, 36 patients with chondroblastoma of the adjoining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The symptoms in many reports include local pain, swelling, joint stiffness and/or effusion, and the development of a limp [36, 2123]. Physical examination may reveal swelling, local tenderness, joint effusion, or local mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The symptoms in many reports include local pain, swelling, joint stiffness and/or effusion, and the development of a limp [36, 2123]. Physical examination may reveal swelling, local tenderness, joint effusion, or local mass.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, CB is characterized by round or polyhedral chondroblasts with a central, longitudinal nuclear groove (“coffee bean” nucleus). In the majority of lesions, islands of cartilage or chondroid matrix can be found [6, 2123]. Edel et al considered that the microscopic appearance of CB can be distinguished from that of other cartillage-containing tumors, such as giant cell tumors of aneurysmal bone cysts [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mashhour and Abdel Rahman [21] preferred aggressive surgical treatment at the time of the rst surgery to prevent recurrence, because re-operation after recurrence might cause more damage on growth plate. Liu Q et al [22] also reported that intraregional aggressive curettage, phenolization, and allogeneic bone grafting were effective for treatment of chondroblastoma with low recurrence. However, lesions extended through the epiphyseal plate or an aggressive curettage does lead to epiphyseal plate injury.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of CB occurrence between men and women is approximately 3:2. This type of tumors often affect the proximal epiphysis of the femur, humerus, and tibia [2,3] , while those affecting the patella are extremely rare [4,5] . Only a few cases of CB combined with secondary ABC [6] have been reported until date, and they can be easily misdiagnosed as giant cell tumor (GCT) or ABC.…”
Section: Introductionmentioning
confidence: 99%